2006
DOI: 10.1063/1.2186307
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed-field ionization electron spectroscopy of group 6 metal (Cr, Mo, and W) bis(benzene) sandwich complexes

Abstract: Group 6 metal bis(benzene) sandwich complexes (M-bz(2): M=Cr, Mo, and W and bz=C(6)H(6)) were produced with laser vaporization molecular beam techniques and studied by pulsed-field ionization zero electron kinetic energy spectroscopy and density functional theory calculations. Each sandwich complex is in a D(6h) eclipsed configuration with (1)A(1g) and (2)A(1g) as the neutral and cationic ground electronic states, respectively. The adiabatic ionization energies for Cr-, Mo-, and W-bz(2) are measured to be 44,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
69
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 52 publications
0
69
0
Order By: Relevance
“…27 The field dependence of the ZEKE signal was not measured because the energy shift from the small electric field ͑1.2 V/cm͒ has been shown to be much smaller than the spectral linewidth. 28 Calculations of molecular geometries and vibrational frequencies were carried out with GAUSSIAN03 program package. 29 The B3LYP ͑Becke's three parameter hybrid functional with the correlation functional of Lee, Yang, and Parr͒ functional was selected because previous studies have shown that this method yielded good agreement with experimental ZEKE spectra of metal-aromatic complexes.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 The field dependence of the ZEKE signal was not measured because the energy shift from the small electric field ͑1.2 V/cm͒ has been shown to be much smaller than the spectral linewidth. 28 Calculations of molecular geometries and vibrational frequencies were carried out with GAUSSIAN03 program package. 29 The B3LYP ͑Becke's three parameter hybrid functional with the correlation functional of Lee, Yang, and Parr͒ functional was selected because previous studies have shown that this method yielded good agreement with experimental ZEKE spectra of metal-aromatic complexes.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
“…29 The B3LYP ͑Becke's three parameter hybrid functional with the correlation functional of Lee, Yang, and Parr͒ functional was selected because previous studies have shown that this method yielded good agreement with experimental ZEKE spectra of metal-aromatic complexes. 28,30,31 In these calculations, the all electron 6-311+ G͑d , p͒ basis was used for all atoms.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
“…High lying Rydberg states of atoms and molecules have found interest in general [1][2][3][4] and particular utility in various spectroscopies; pulsed field ionization-zero electron kinetic energy (PFI-ZEKE) [5][6][7][8] and threshold ionization mass spectrometry [9][10][11][12][13] to name a few. Both techniques rely on the ability to optically pump electronic transitions to Rydberg energy levels near ionization.…”
Section: Introductionmentioning
confidence: 99%
“…[8] and the ZEKE spectrum from ref. [13]. The spectral resolution of the ZEKE spectrum is about one-hundred times better than that of the He 1 spectrum.…”
Section: Introductionmentioning
confidence: 97%
“…In this figure, the He I photoelectron spectrum of bis(benzene)chromium is broad (~ 60 meV) [8], whereas its ZEKE spectrum is very sharp (~ 0.6 meV) with well-resolved metal-ligand vibrational structures [13]. ZEKE is different from traditional photoelectron spectroscopy in that ionization is not direct but stepwise (Figure 2).…”
Section: Introductionmentioning
confidence: 97%